2005
DOI: 10.1111/j.1365-2567.2005.02234.x
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation of T‐cell proliferation by anti‐l‐selectin antibody is associated with the reduction of a cdk inhibitor p27

Abstract: SummaryIn this study, we investigated the costimulatory activity of L-selectin in primary mouse T cells. Proliferation induced by immobilized anti-CD3 antibody was enhanced by immobilized anti-L-selectin antibody. In contrast to the anti-CD28 antibody, anti-L-selectin antibody did not enhance interleukin-2 (IL-2) expression. One of the cyclin-dependent kinase (cdk) inhibitors, p27, was reduced by costimulation with anti-L-selectin antibody, as with anti-CD28 antibody, suggesting that the enhancement of T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Our in vitro studies confirmed that CD62L mediates OVA-induced γδ T lymphocyte proliferation, suggesting defective co-stimulatory signaling during antigen presentation. Supporting reports demonstrated that CD62L co-stimulation with specific antibody enhanced α-CD3 mAb-induced proliferation and expression of CD25 on T lymphocytes [24]. In addition, the inhibition of CD62L signaling blocked α-CD3 mAb-induced T cell proliferation, due to impaired activation, as determined by calcium influx and ZAP-70 phosphorylation [35].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our in vitro studies confirmed that CD62L mediates OVA-induced γδ T lymphocyte proliferation, suggesting defective co-stimulatory signaling during antigen presentation. Supporting reports demonstrated that CD62L co-stimulation with specific antibody enhanced α-CD3 mAb-induced proliferation and expression of CD25 on T lymphocytes [24]. In addition, the inhibition of CD62L signaling blocked α-CD3 mAb-induced T cell proliferation, due to impaired activation, as determined by calcium influx and ZAP-70 phosphorylation [35].…”
Section: Discussionmentioning
confidence: 91%
“…On the right, representative dot plots show percentages of pleural CCL11 + γδ, IL-5 + γδ and IL-4 + γδ T lymphocytes. molecules are capable to associate with TCR/CD3 complex [24][25][26]. The fact that in vivo selectin blockade both impaired OVA-induced increased numbers of γδ T lymphocytes in thoracic lymph nodes and reduced the numbers of γδ T cells expressing the proliferating phenotype IL-2α receptor chain CD25 and c-fos transcriptional factor suggests diminished activation and primary proliferating responses [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, together with the observation that T cells isolated from inflammatory sites express low levels of CD62L (10 -12), have suggested that down-regulation of CD62L may be required to redirect activated T cells away from LN, however this hypothesis has not been tested directly. Although the primary function of CD62L is in LN homing, expression levels correlate directly with effector function of CD8 T cells (13) and signaling via CD62L has been shown to costimulate TCR proliferation (14). It is, therefore, possible that the level of CD62L expression may also regulate the proliferation, differentiation and/or survival of Ag-activated T cells.…”
mentioning
confidence: 99%
“…The protein concentrations were determined using bicinchoninic acid (Sigma Chemical, MO, USA) with bovine serum albumin as a standard. An equal amount of protein was loaded on each lane of a 7.5% polyacrylamide gel and transferred to PVDF membrane followed by the detection with anti-YY1 antibody as reported previously (Nishijima et al 2005).…”
Section: Western Blottingmentioning
confidence: 99%